Imágenes de una catástrofe. El terremoto de Melfi de 1851 en la obra de Salvatore Fergola - Fernandez Martinez, Carla (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2018)
One of the most destructive earthquakes in southern Italy was the one happened in 1851 in the Basilicata region, with particularly strong effects in the city of Melfi. The earthquake coincided with the last years of the Bourbon government and, for this reason, some of the actions promoted by the monarchy were aimed to highlight the measures adopted to alleviate the damage. As a result of this interest, certain relationships and official accounts were created to describe the losses caused and the reconstruction processes. Those mentioned chronicles are, together with the preserved graphic testimonies, one of the most outstanding primary sources for their knowledge. Precisely, in the following pages it is presented a study on the urban iconography of the devastated city of Melfi, centered, above all, on the representations bequeathed by the painter Salvatore Fergola.